Enterprise Architecture Design of Information Media at Little Ambulance in Sumedang Regency - Dewi, Sofia; Wijaya, Miki; Prakarsa A.S, Muhammad (CV. Generasi Intelektual Digital, 2024)
In this modern era, disseminating information is easier and faster through the latest technology, including publications using information media. Little Ambulance is a social institution in the field of public health which requires information media to build public trust. Enterprise Architecture (EA) is a reference framework used to build an information architecture that suits the needs of Little Ambulance. Little Ambulance, by using this EA, is able to identify ongoing transactions and operations and also to design a blueprint for the future. The required information architecture includes information about location, news, volunteer search, and donation transaction reports. Creating this website can help Little Ambulance to gain trust, support and volunteers who want to join, as well as to ensure transparency of expenditure made by Little Ambulance in order to increase public trust.